The fiscal and distributional implications of job generation - Kitson, M; Michie, J; Sutherland, H (Cambridge Political Economy Society, 1997)
This article estimates the cost of a public investment-led job creation programme for the United Kingdom. A programme creating an additional one million jobs at the current average wage would involve a net cost to the Treasury dramatically lower than the gross cost; £17 billion worth of spending would result in a net cost of around £7 billion. Given that even a partial restoration of progressive taxation would bring in more than half this net amount, improved living standards could be brought about relatively easily, provided dogmatic objections to public sector initiatives can be overcome.